Different characteristics between auctioned and non-auctioned patents - Lee, Yong-Gil; Lee, Ji-Hoon (SPRINGER, 2010)
In recent years, firms have increased their use of internal and external knowledge through intermediaries. Knowledge brokers match buyers and sellers in the technology marketplace as well as connect and combine existing knowledge. We discuss how financial incentives in the technology marketplace can address challenges to open innovation, and how the marketplace could make individual inventors essential contributors. And then, we identify the key determinants of intellectual-property auction bids and different characteristics of auctioned and non-auctioned patents. Relevance, the scope of patents, and other factors suggested in the literature impact patent auctions, as mediated by knowledge brokers.
Keywords: INNOVATION; MARKET